Policy Responses to External Imbalances in Emerging Market Economies : Further Empirical Results - Carranza, Luis (IMF Working Papers; Working Paper, 1998)
A bivariate vector-autoregression (VAR) model is used to test causal relations between the current account and the capital account in four emerging market economies. The results show that high capital mobility could be a major cause of current account instability. Therefore, macroeconomic policy to restore external balance must deal directly with capital inflows. The paper recommends making nominal exchange rate sufficiently flexible to avoid inconsistencies between short-run and long-run real exchange rates; complementing credit tightening by fiscal restraint to reduce interest rate differentials; and strengthening reforms and surveillance of the financial system to prevent banks from excessive risk taking.